1980
DOI: 10.1073/pnas.77.1.152
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus-induced modification of cap-dependent translation in infected L cells.

Abstract: The translational apparatus in cell-free extracts prepared from L cells infected with reovirus undergoes a time-dependent transition from cap dependence to cap independence. Extracts from uninfected L cells translate capped reovirus mRNA at high efficiency and synthesize the expected three size classes of reovirus polypeptides, and the translation is sensitive to m7G(5')ppp. This same extract translates uncapped mRNA at a much lower efficiency. In contrast, extracts from infected L cells translate uncapped reo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1

Year Published

1984
1984
1997
1997

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 33 publications
(20 reference statements)
3
41
1
Order By: Relevance
“…Contrary to Skup and co-workers (Skup & Millward, 1980;Skup et al, 1981) and in agreement with Detjen et al (1982), the results obtained led us to consider that reovirus-infected HeLa cells are able to translate capped viral mRNAs late during virus infection. However, in reovirus-infected HeLa cells, no inhibition of cellular protein synthesis is apparent at the time when most viral proteins are synthesized, which suggests that there is an excess of translation components and that no competition between cellular and viral mRNAs is established in intact infected cells.…”
Section: Introductioncontrasting
confidence: 51%
See 4 more Smart Citations
“…Contrary to Skup and co-workers (Skup & Millward, 1980;Skup et al, 1981) and in agreement with Detjen et al (1982), the results obtained led us to consider that reovirus-infected HeLa cells are able to translate capped viral mRNAs late during virus infection. However, in reovirus-infected HeLa cells, no inhibition of cellular protein synthesis is apparent at the time when most viral proteins are synthesized, which suggests that there is an excess of translation components and that no competition between cellular and viral mRNAs is established in intact infected cells.…”
Section: Introductioncontrasting
confidence: 51%
“…Contrary to this view, Skup & Millward (1980) have suggested that the inhibition of translation after reovirus infection of L cells occurs by a mechanism similar to that already suggested for poliovirus. The model proposes that the reovirus mRNA synthesized early in infection is capped, and the infected cells translate this kind of mRNA efficiently, but not uncapped mRNAs.…”
Section: Introductionmentioning
confidence: 57%
See 3 more Smart Citations